Breaking the rules : a fresh take on Italian classics - Sasto, Joe; Baumann, Thea (Simon Element, 2025)
It's time to ditch the same boring recipes and get creative in the kitchen. Known for his signature curled mustache and dynamic presence on shows like Bravo's Top Chef and Food Network's Tournament of Champions, Joe Sasto brings his culinary expertise and passion for pasta to your kitchen. Breaking the Rules is a celebration of Italian cuisine, reimagined with Joe's unique flair, playfulness, and creativity. Dive into a world of pasta with step-by-step techniques that guide you through creating dishes in all forms, shapes, and sizes. From classic Italian recipes like meatballs and focaccia to innovative creations such as Corn Cacio e Pepe, Marinated Tomato "Amatriciana," and Pesto Pinwheel Pull-Apart Bread, Joe's recipes are designed to inspire both novice and experienced cooks. Each recipe begins with a simple version, perfect for beginners, and offers variations to elevate the dish for those ready to "break the rules" and take their skills to the next level. --